ANALISIS METODE ECONOMIC VALUE ADDED DAN MARKET VALUE ADDED SEBAGAI PENGUKUR KINERJA KEUANGAN PERUSAHAAN - Sindina Nur Malasari, Rispantyo & Djoko Kristianto (Universitas Slamet Riyadi, 2016)
The purpose of this study was to determine the financial performance of companies by using Economic Value Added and Market Value Added. This study uses a case study on PT Bumi Serpong Damai and its subsidiaries listed in BEI period of 2011-2014. This type of research is descriptive analysis method Economic Value Added and Market Value Added. The data used is secondary data. This research object is PT Bumi Serpong Damai and its subsidiaries listed on the Stock Exchange.The result of this research is PT Bumi Serpong Damai and its subsidiaries already shown positive results with the method of Economic Value Added and Market Value Added methods.Keywords: Economic Value Added, Market Value Added, Financial Performance